Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/ange.201710637
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Activated Delayed Fluorescence in a Y3N@C80 Endohedral Fullerene: Time‐Resolved Luminescence and EPR Studies

Abstract: Abstract:The endohedral fullerene Y 3 N@C 80 exhibits luminescence with reasonable quantum yield and extraordinary long lifetime.B yv ariable-temperatures teady-state and timeresolved luminescence spectroscopy, it is demonstrated that above6 0Kthe Y 3 N@C 80 exhibits thermally activated delayed fluorescence with maximum emission at 120 Kand anegligible prompt fluorescence.B elow 60 K, ap hosphorescence with al ifetime of 192 AE 1msi so bserved. Spin distribution and dynamics in the triplet excited state is inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Thermally-activated delayed uorescence (TADF) described for Y 3 N@C 80 (ref. 51) and empty fullerenes 56 probably take place in all Y x Sc 3Àx N@C 80 compounds. This hypothesis is further corroborated via temperature-dependent PL study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thermally-activated delayed uorescence (TADF) described for Y 3 N@C 80 (ref. 51) and empty fullerenes 56 probably take place in all Y x Sc 3Àx N@C 80 compounds. This hypothesis is further corroborated via temperature-dependent PL study.…”
Section: Resultsmentioning
confidence: 99%
“…49,50 Recently we found that the strong photoemission of Y 3 N@C 80 is caused by the small singlet-triplet S 1 -T 1 gap of less than 0.1 eV, which enables thermally activated delayed uorescence (TADF) via thermal population of the emitting S 1 state from the T 1 "reservoir". 51 As the triplet state plays a crucial role in the process, in the same work we also characterized its dynamics and spin distribution by light-induced EPR and ENDOR spectroscopy and found that yttrium atoms have negligible spin populations. TADF is a crucial phenomenon for this work, and Fig.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations